Comparison of Wound Infection between Open Lichtenstein Mesh repair and Laparoscopic Transabdominal Preperitoneal (TAPP) repair in Inguinal Hernia - Rab Nawaz Malik, Faisal Ali, Aqeel Masood, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the wound infection between Open Lichtenstein mesh repair and Laparoscopic transabdominal preperitoneal (TAPP) repair in inguinal hernia. Materials and Methods: Between May 2021 to November 2021, total 262 patients of inguinal hernia either male or female, age 18-60 years with ASA grade I & II were selected from Department of Surgery, Bakhtawar Amin Medical and Dental College Multan. Type of study was randomized controlled trial. Wound infection, mean pain score and mean duration of hospital stay was compared between the groups. Results: Mean age was 38.46 ± 12.88 years, mean age in Open group and Laparoscopic group was 38.21 ± 13.28 years and 38.70 ± 12.51 years. In Open group, wound infection was noted in 38 (29.01%) patients while in Laparoscopic group was 13 (9.92%) patients. Difference of wound infection between the both groups was significant (P=0.000). Mean pain score in Open group and Laparoscopic group was 3.66 ± 2.57 and 2.76 ± 2.61 respectively. Mean hospital stay in Open group was 3.18 ± 0.799 days while in Laparoscopic group was 4.65 ± 1.007 days. Conclusion: Results of present study showed that males are more victim of inguinal hernia as compared to females. Higher proportion of patients was found with wound infection in patients managed with Open Lichtenstein mesh repair method as compared to Laparoscopic transabdominal preperitoneal method. Keywords: TAPP, Inguinal hernia, open Lichtenstein mesh repair, wound infection